Victims or suspects? Identifying and assisting potentially trafficked fishermen: A qualitative study with stakeholders and first responders in Thailand - Nicola S Pocock; Heidi Stöckl; Reena Tadee; Wansiri Rongrongmuang; Kanokwan Tharawan; Fiona B Adamson; Cathy Zimmerman (Elsevier, 2021)
Prompted by reports of 'sea slavery' in the fishing industry and threats of sanctions, Thailand has faced pressure to eradicate human trafficking the fishing sector. Although the Thai government has responded with anti-trafficking policies, there remains little understanding about their implementation. Specifically, little is known about how government agencies, NGOs or industry perceive "trafficking", and no research examines how trafficked fishermen are identified and assisted. This study aimed to: 1) explore how stakeholders described trafficking in the fishing sector and their perceptions of trafficking indicators; and 2) identify challenges encountered by frontline responders to identify and assist trafficked fishermen. We conducted interviews with 33 key informants, which were analysed thematically. Findings indicate that authorities and industry representatives believed migrant brokers caused employers to "inadvertently" traffic men. Trafficking was perceived to take place primarily outside of Thai waters, beyond the government's jurisdiction. Most stakeholders considered violence and being confined as key indicators of trafficking. Officials expressed confusion about whether debt bondage and document confiscation "counted" as indicators. Ambiguity and confusion about trafficking indicators in screening forms, combined with perceived "deservingness" of official victim status, underpinned frontline responders' decisions about who was a victim of trafficking (VoT). Practical and structural constraints included interpreter shortages, and expanded civil servant remits without commensurate staff increases, which hindered officials' responses to trafficking. This study addresses a critical knowledge gap on the implementation of anti-trafficking policies and offers findings to assist policymakers to address the challenges faced by frontline responders to improve victim identification and assistance.